2006
DOI: 10.1097/01.olq.0000187908.42622.fd
|View full text |Cite
|
Sign up to set email alerts
|

Condom Use and Risk of Gonorrhea and Chlamydia: A Systematic Review of Design and Measurement Factors Assessed in Epidemiologic Studies

Abstract: Condom use was associated with reduced risk of gonorrhea and chlamydia in men and women in most studies, despite methodologic limitations that likely underestimate condom effectiveness. Epidemiologic studies that better address these factors are needed to provide more accurate assessment of condom effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(110 citation statements)
references
References 103 publications
4
104
0
2
Order By: Relevance
“…139 In a systematic review the protective effect for chlamydia ranged from 10% to 90%, and for gonorrhoea ranged from 13% to 100%. 140 The authors reported that studies that were limited to individuals with known STI exposure were likely to estimate the protective effect of condom use more accurately. Niccolai and colleagues 141 estimated the effectiveness of condoms for the prevention of chlamydia among people who were exposed to the infection and found that consistent condom use was significantly associated with a 90% reduction in the prevalence of chlamydia.…”
Section: Condom Effectivenessmentioning
confidence: 99%
“…139 In a systematic review the protective effect for chlamydia ranged from 10% to 90%, and for gonorrhoea ranged from 13% to 100%. 140 The authors reported that studies that were limited to individuals with known STI exposure were likely to estimate the protective effect of condom use more accurately. Niccolai and colleagues 141 estimated the effectiveness of condoms for the prevention of chlamydia among people who were exposed to the infection and found that consistent condom use was significantly associated with a 90% reduction in the prevalence of chlamydia.…”
Section: Condom Effectivenessmentioning
confidence: 99%
“…Polyurethane condoms are relatively thin and odorless. They provide comparable protection as of latex condoms against various STIs [60]. However, polyurethane condoms are at higher risk of breakage during intercourse.…”
Section: Puting the Physical Barriers To Stismentioning
confidence: 99%
“…Consistent and correct condom use in penetrative vaginal and anal sex has been demonstrated as an effective way of preventing HIV transmission (7). Condoms also prevent the transmission of other sexually transmitted infections such as syphilis and gonorrhea.…”
Section: Condoms and Hiv Preventionmentioning
confidence: 99%